Juridical Analysis Of The Authority Of The Marine And Coast Guard Base In Carrying Out Its Duties: Research Study at Tanjung Uban Class II PLP Base - Orie Andriyanto; M. Soerya Respationo; Erniyanti Erniyanti; Ramlan Ramlan; Dahlan Dahlan (International Journal of Law and Society, 2024)
The Sea and Coast Guard Base (PLP) plays a vital role in maintaining maritime security and safety in Indonesia, especially in strategic waters such as the Riau Islands. However, the implementation of the PLP's authority in carrying out its duties at the Tanjung Uban Class II PLP Base has not run optimally. This study aims to analyze the authority of the PLP from a juridical and sociological perspective, as well as identify the obstacles faced and provide recommendations to overcome them. The research methods used are normative juridical and empirical sociology. The normative juridical method is used to analyze various laws and regulations that are the legal basis for the authority of the PLP, such as Law Number 17 of 2008 concerning Shipping, Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 119 of 2021 concerning the Organization and Work Procedures of Marine and Coast Guard Bases, Decree of the Director General of Hubla Number 13/VIII/DV-05 of 2005 concerning the Working Area of Marine and Coast Guard Bases and the Decree of the Director General of Sea Transportation Number KP.867/DJPL/2020 concerning the Patrol of the Marine and Coast Guard Unit of the Directorate General of Sea Transportation. Empirical sociological methods are used to collect data through interviews and direct observations in the field to understand the implementation of PLP authority and the obstacles faced. The results of the study show that limited human resources and equipment, lack of coordination between agencies, inadequate infrastructure, and complex bureaucracy are the main obstacles in the implementation of PLP authority in the Tanjung Uban Class II PLP Base. In addition, the low legal awareness among the maritime community is also a significant challenge. Based on these findings, this study provides several suggestions, including increasing recruitment and training of personnel, procurement and maintenance of patrol boats and supporting equipment, the formation of an inter-agency coordination team, the construction of adequate port facilities, and socialization and education to increase public legal awareness. This research is expected to contribute to strengthening policies and strategies for the implementation of PLP authority, so as to be able to increase effectiveness and efficiency in maintaining maritime security and safety in Indonesian waters.